Burn notice. Season six [videorecording (DVD)] - Surjik, Stephen; Donovan, Jeffrey; Anwar, Gabrielle; Campbell, Bruce, 1958- (Twentieth Century Fox Home Entertainment, 2013)
After he is suddenly kicked out of his job as a government contract spy, Michael Weston returns to his home town of Miami to figure out who is behind the firing while offering his services to those in need.